An early life course association of pulse pressure with adulthood estimated glomerular filtration rate: evidence from a large community-based birth cohort study. Issue 2 (February 2017) - Das, Sumon K.; McIntyre, Harold D.; Mamun, Abdullah Al
Abstract : Background: Little is known about pulse pressure (PP) during early life and its association with renal function at young adulthood. This study describes an early life course association of PP with adult renal function at 30 years from a large community-based birth cohort study in Australia. Method: Sample comprises 1169 young adults aged 30 years from the Mater-University of Queensland Study of Pregnancy, whose blood pressure was recorded in at least three follow-ups (5, 14, 21, and 30 years) and renal function was assessed at 30 years. Estimated glomerular filtration rate was estimated to determine the stages of chronic kidney disease (CKD). A group-based trajectory modelling was developed to identify patterns of PP from childhood to adulthood. Multiple logistic regression was used to determine whether PP trajectories predict adult CKD. Results: In total, 7% of participants (91) had mild CKD. Three PP trajectories were identified: 16% were in the high PP trajectory group characterized by substantial increase in PP over time; 58% were in the middle group who had lower PP at 5 years, which increased at 14 years and then gradually declined at 21 and 30 years, and the remaining 26% were in a lower group which remained static. In the adjusted model, significantly higher odds were found for the high [odds ratio: 2.42 (95% confidence interval: 1.02–5.74)] and middle [2.23 (1.19–4.19)] PP trajectory groups for development of mild CKD at 30 years compared with the low (static) group. Conclusion: Early life high and middle PP trajectories predict the risk of subclinical renal insufficiency by age 30 years. Abstract : Supplemental Digital Content is available in the text